Development of asymmetric polyethersulfone (PES) mixed Matrix membrane for O2/N2 separation - Nurul Farhanah, Che Bahar (2010)
The latest rising of polymer-based organic-inorganic composite membrane materials known as mixed matrix membranes (MMMs), have potentially to combine the easy processability of organic polymers with the excellent gas separation properties of inorganic molecular sieve material. In this study, the development of mixed matrix membranes for oxygen/nitrogen (O2/N2) separation by manipulating the different types of zeolite was studied in order to identify the best composition of zeolite. Three types of zeolite were used are 4A, 5A and 13X. To enhance the adhesion of zeolite with polymer matrix and also to modify the surfaces of inorganic material, 3-aminopropyltrimethoxysilane (APTMOS) was introduced to treat the zeolite prior to dope solution preparation. The polymer solution consists of 30 wt% of polyethersulfone (PES) as polymer, 60 wt% of n-methyl-pyrrolidone (NMP) as solvent, 5 wt% of distilled water as non solvent and 5 wt% of different types of zeolite. Asymmetric flat sheet mixed matrix membranes were fabricated using manually casting through dry/wet phase inversion process. Membrane produce was coated with polydimethylsiloxane (PDMS) to produce defects-free membrane. Then, the membrane was tested with the pure oxygen (O2/N2) gases and nitrogen gases by using the permeation test unit with the feed pressure range between 1 to 5 bars. From the pure gas permeation test result, it shows that the MMMs incorporation with zeolite 4A produce the highest selectivity, which is 3.2 and the lowest selectivity can be achieved using zeolite 13X and the selectivity was 1.7 at the optimum pressure of 2 bars. The differences of selectivity value between difference zeolite are because of the pore size of the zeolite. The morphology of prepared membrane had been identified by using Scanning Electron Microscope (SEM). As a conclusion, by adding the polymer solution with different type of zeolite will exhibit difference membrane performance. It is because of difference zeolite have different pore size. It also proves that, by adding zeolite 4A, the selectivity of O2/N2 is increased.